Cell Wall Surface Properties of Kluyveromyces marxianus Strains From Dairy-Products - Perpetuini, Giorgia; Tittarelli, Fabrizia; Suzzi, Giovanna; Tofalo, Rosanna (Frontiers in Microbiology, 2019)
Thirty-three K. marxianus strains were tested for the ability to form biofilm and mat structures in YPD and whey and for cell surface hydrophobicity. To identify genes potentially involved in adhesion properties, a qPCR analysis was performed. Eight strains were able to adhere on polystyrene plates in both media and formed a mature mat structure. These strains showed a different level of hydrophobicity ranging from 55% to 66% in YPD and from 69% to 81% in whey. Four K. marxianus orthologues genes (FLO11, STE12, TPK3 and WSC4), known from studies in other yeast to be involved in biofilm formation, have been identified. FLO11 and STE12 showed the highest fold changes in all conditions tested and especially in whey: 15.05 and 11.21, respectively. TPK3 was upregulated only in one strain, and WSC4 in 3 strains. In YPD, fold changes were lower than in whey with STE12 and FLO11 genes showing the highest fold changes. In mat structures FLO11 and STE12 fold changes ranged from 3.6 to 1.3 and from 2 to 1.17, respectively. Further studies are necessary to better understand the role of these genes in K. marxianus adhesion ability.